Lignocellulosic xylitol production from corncob using engineered Kluyveromycesmarxianus - Zhang, Jia; Xu, Teng; Wang, Xiaohang; Jing, Xiaoyan; Zhang, Jia; Hong, Jiong; Xu, Jian; Wang, Jichao (Frontiers in Bioengineering and Biotechnology, 2022)
Xylitol production from lignocellulose hydrolysate is a sustainable and environment-friendly process. In this study, a systematic process of converting corncob waste into xylitol is described. First, the corncobs are hydrolyzed with acid to a hydrolysate. Second, Kluyveromyces marxianus YZJQ016 derived from K. marxianus YZJ074, constructed by overexpressing ScGAL2-N376F from Saccharomyces cerevisiae, CtXYL1 from Candida tropicalis, and KmZWF1 from K. marxianus, produces xylitol from the hydrolysate. A total of ten xylose reductase genes were evaluated, and CtXYL1 proved best by showing the highest catalytic activity under the control of the KmGAPDH promoter. A 5 L fermenter at 42°C produced 105.22 g/L xylitol using K. marxianus YZJQ016—the highest production reported to date from corncob hydrolysate. Finally, for crystallization of the xylitol, the best conditions were 50% (v/v) methanol as an antisolvent, at 25°C, with purity and yield of 99%–100% and 74%, respectively—the highest yield reported to date.